Pengaruh Metode TPR Storytelling terhadap Keterampilan Berbicara dan Membaca Siswa MTs - Nuryani, Waway; Susiawati, Wati (INCARE, International Journal of Educational Resources, 2025)
Mastery of speaking skills (maharah kalam) and reading skills (maharah qiro’ah) in Arabic is a crucial competency for students at the secondary level. Effective learning methods are essential to improve these two skills so that students can communicate and understand Arabic optimally. This study aims to examine the effectiveness of the Total Physical Response Storytelling (TPRS) method in teaching speaking and reading skills to seventh-grade students at MTsS Ma’had Al Zaytun. The study was designed to compare learning outcomes between a class using the TPRS method and a class using conventional teaching methods. The research method used was quantitative with a quasi-experimental design, involving two groups: an experimental class that used the TPRS method and a control class with conventional teaching methods. The research population consisted of 407 students, with a sample of 60 students taken for each group. Data were collected through observation, interviews, speaking and reading pretests and posttests, and questionnaires. The results showed that the average posttest score for the experimental class's speaking ability was 88.47, while the control class's was 67.83. For reading skills, the average posttest score for the experimental class was 86.82 and 66.02 for the control class. A statistical t-test showed a t-value of 24.29 for speaking and 21.29 for reading with a significance of 0.000 (<0.05), proving the significant effectiveness of the TPRS method in improving students' Arabic speaking and reading skills.